Configuration of Assets of Criminal Offenders Taxation From A Perspective Criminal Procedure Law - Defry Romandhany; Sahuri Lasmadi; Herry Liyus (Journal of Law, Politic and Humanities, 2024)
The aim of this research is first, to determine and analyze the confiscation of assets of perpetrators of tax crimes from the perspective of criminal procedural law. Second, to find out and analyze future criminal law policies regarding the regulation of confiscation of assets of perpetrators of tax crimes from the perspective of criminal procedural law. The legal issues discussed in this normative research are: First, what are the legal regulations for confiscating assets of perpetrators of tax crimes? Second, what will be the future criminal law policy regarding the regulation of confiscation of assets of perpetrators of tax crimes from the perspective of criminal procedural law? The research method used is normative juridical with approaches (Statue Approach, (Conceptual Approach), (case approach), and (comparative approach). The legal material in this research was collected through literature studies, laws, government regulations, as well as regulations under law, journals, and legal cases used by this author. As well as other supporting materials. The results of this research show that the Asset Confiscation Bill is an opportunity to recover state losses in Indonesia. With the existence of an asset confiscation mechanism, eradication law enforcement uses two mechanisms, namely penal and non-penal. This is because, confiscation of assets without criminal prosecution does not eliminate the mechanism for criminal prosecution of the perpetrator's crimes in court. The scheme used by developed countries in connection with the confiscation of assets resulting from criminal acts is unexplained wealth. In the context of the Indonesian legal system, there is a need for reform both in terms of juridical, concept and paradigm which must be carried out synergistically and sustainably. Therefore, to enforce unexplained wealth, there must be a comprehensive and accommodating regulatory framework as shown in the Criminal Asset Confiscation Bill.